THE LINKAGE BETWEEN INTANGIBLES AND PROFITABILITY - TUDOR, Adriana Tiron; DIMA (CRISTEA), Ștefana; DIMA, Bogdan; RAȚIU, Raluca Valeria (Annales Universitatis Apulensis Series Oeconomica, 2014)
The intangibles can be viewed as strategic assets, since their inclusion in the structure of the total assets allows economic entities to extract a “competiveness rent” and, thus, to enhance the outcomes of their activity. This paper seeks to provide some empirical evidences for the effects exercised by shocks emerged at the level of intangible-to-total assets ratio on profitability in the case of 562 large companies listed on Frankfurt Stock Exchange and London Stock Exchange. We found that, for the full sample, there is a relatively steady relationship between this ratio and various measures of profitability (Return on Assets - ROA, Return on Capital Employed – ROCE and Gross Margin). However, when the two markets as whole or different sectors are considered, there seem to be various significant structural differences and some scale effects in the transmission of the intangibles’ impact on profitability. Moreover, we check the robustness of the results in view of two control variables: cash flow-to-operating revenue ratio appears to be the most robust, whereas the effects of solvability ratio are less stable and vary across markets and sectors